Smith’s predictor and feedforward disturbance compensation for ATM congestion control - L.A. Grieco; S. Mascolo (Proceedings of the 41st IEEE Conference on Decision and Control, 2002., 2002)
This paper proposes an end-to-end congestion control algorithm for available bit rate traffic in high-speed ATM networks. The feedback control law is designed using the Smith principle. Moreover, a feedforward disturbance compensation is added to improve the performance of the control system. The control algorithm is rate based and does not require any explicit feedback from the network. We test the proposed control algorithm over the generic fairness configuration 2 scenario, which is a standard benchmark with multiple bottlenecks and large round trip delays proposed by the ATM forum. Simulation results show that the proposed algorithm provides performance indexes comparable or slightly better than those obtained by the ERICA switch algorithm, which is the leading algorithm in the ATM community, even though ERICA requires explicit support from network nodes.
Keywords: Asynchronous transfer mode; Communication system traffic control; Switches; Bit rate; Feedback control; Feedforward systems; Delay; Performance analysis; Switching circuits; Packet switching